Substituted dienes prepared from betulinic acid - Synthesis, cytotoxicity, mechanism of action, and pharmacological parameters - Pokorný, Jan; Olejníková, Denisa; Frydrych, Ivo; Lišková, Barbora; Gurská, Soňa; Benická, Sandra; Šarek, Jan; Kotulová, Jana; Hajdúch, Marián; Džubák, Petr; Urban, Milan (European journal of medicinal chemistry, 2021)
A set of new substituted dienes were synthesized from betulinic acid by its oxidation to 30-oxobetulinic acid followed by the Wittig reaction. Cytotoxicity of all compounds was tested in vitro in eight cancer cell lines and two noncancer fibroblasts. Almost all dienes were more cytotoxic than betulinic acid. Compounds 4.22, 4.30, 4.33, 4.39 had IC50 below 5 μmol/L; 4.22 and 4.39 were selected for studies of the mechanism of action. Cell cycle analysis revealed an increase in the number of apoptotic cells at 5 × IC50 concentration, where activation of irreversible changes leading to cell death can be expected. Both 4.22 and 4.39 led to the accumulation of cells in the G0/G1 phase with partial inhibition of DNA/RNA synthesis at 1 × IC50 and almost complete inhibition at 5 × IC50. Interestingly, compound 4.39 at 5 × IC50 caused the accumulation of cells in the S phase. Higher concentrations of tested drugs probably inhibit more off-targets than lower concentrations. Mechanisms disrupting cellular metabolism can induce the accumulation of cells in the S phase. Both compounds 4.22 and 4.39 trigger selective apoptosis in cancer cells via intrinsic pathway, which we have demonstrated by changes in the expression of the crucial apoptosis-related protein. Pharmacological parameters of derivative 4.22 were superior to 4.39, therefore 4.22 was the finally selected candidate for the development of anticancer drug.
Keywords: psi; alkadieny; pentacyklické triterpeny; kyselina betulinová; vztahy mezi strukturou a aktivitou; Cell cycle; buněčný cyklus; Molecular Structure; proliferace buněk; Cytotoxicity; Triterpene; screeningové testy protinádorových léčiv; Apoptosis; Cell Cycle; Humans; Cells, Cultured; Dogs; Antineoplastic Agents; Pentacyclic Triterpenes; lidé; vztah mezi dávkou a účinkem léčiva; Cell Proliferation; Structure-Activity Relationship; Drug Screening Assays, Antitumor; Animals; Dose-Response Relationship, Drug; apoptóza; zvířata; Selectivity; Mechanism of action; protinádorové látky; Cancer; Wittig reaction; kultivované buňky; Betulinic acid; molekulární struktura; Alkadienes; Betulinic Acid